PENGGUGATAN KANONISASI SASTRA MELALUI MEDIA SIBER KARYAKARSA - Pramudya Adi Pratama; Rianna Wati (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2022)
The development of information and communication technology has had a major influence on modern human life. One of them is in the field of literature which is marked by the emergence of cyber literature in digital form. The distribution process through the internet has brought new changes to a more efficient production because it does not rely on conventional printing tools with large capital. Every society has the same opportunity as an author who is free to express and explore his work without the attachments and constraints of literary legitimate bodies that carry out canonization practices. This difficult selection process is a reinforcing motive for why cyber literature is growing and in demand, because authors and readers spend less effort to create, distribute, or access other people's works. In the realm of cyber literature, financial security is not that great for the author. This has led to various cyber literary media in the form of applications and websites that are easily accessible but with royalty regulations that provide full benefits without discounting distribution and production duties as in the conventional distribution of printed works. The research in this article uses descriptive qualitative methods by analyzing the object of study and documenting the study as reinforcing data.